2013
DOI: 10.1136/bjophthalmol-2013-303841
|View full text |Cite
|
Sign up to set email alerts
|

Anterior and posterior capsular opacification with the Tecnis ZCB00 and AcrySof SA60AT IOLs: a randomised intraindividual comparison

Abstract: Both IOLs had a similar low rate of PCO 1 year after surgery. However, there seems to be a difference in the anterior capsule behaviour between both IOL models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
0
17
2
1
Order By: Relevance
“…Of the original 160 eyes (80 patients) enrolled, 12 (6) were excluded because of a large and nonoverlapping CCC and 48 (24) were lost to follow-up or were excluded because of insufficient retroillumination image quality. All surgeries were uneventful.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the original 160 eyes (80 patients) enrolled, 12 (6) were excluded because of a large and nonoverlapping CCC and 48 (24) were lost to follow-up or were excluded because of insufficient retroillumination image quality. All surgeries were uneventful.…”
Section: Resultsmentioning
confidence: 99%
“…Eyes with an IOL with an interrupted square optic edge had statistically significantly higher percentages of ACO and higher ACO scores than eyes with a continuous square optic edge IOL; this is similar to the 1-year results in a previous study evaluating the same 2 IOL models. 6 Because IOLs were implanted in fellow eyes of the same patient, we assume that factors inherent in the individual patient can be disregarded (intraindividual comparison). The differences in IOL surface properties and design might explain this finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The intraocular lenses have a role in preventing and promoting posterior capsular changes. 7,8 Lens epithelial cells (LECs) transdifferentiate to myofibroblastic cells, producing collagen fibres around the anterior capsulotomy margins. 1 These fibres cause the anterior capsulotomy margin to adhere to the posterior capsule to form a closed space in which LECs differentiate into lens fibre cells.…”
mentioning
confidence: 99%
“…Kahraman et al 26 recently showed that the square edge design of the two modern IOLs described does not show a significant difference for PCO rates—there is a slight tendency for the AcrySof IOL to develop PCO, anterior capsule opacification, and capsular phimosis faster. A limitation of their study was the short follow-up time of only 12 months, as the usual PCO development for modern IOLs was evaluated in other studies over a period of at least 11–36 months 6 7 9–11 27.…”
mentioning
confidence: 99%